THE ROLE OF COGNITIVE LEARNING TECHNOLOGIES IN THE FORMATION OF LEARNING AND COGNITIVE COMPETENCIES OF STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article briefly describes the essence of cognitive learning technologies and the main directions of their application in education. Examples of applying them in the educational process are given. The pedagogical possibilities of applying technologies for the formation of educational and cognitive competencies of students are discussed.